Investigation of Nanostructured SnO2 Synthesized with Polyol Technique for CO Gas Sensor Applications. (2017) - Debataraja, Aminuddin; Zulhendri, Daryl Widia; Yuliarto, Brian; Nugraha; Hiskia; Sunendar, Bambang
Abstract: In the development of gas sensors, many material based on Metal Oxide Semiconductor is often used, one of them is Tin Oxide (SnO2 ). SnO2 is widely used for CO gas sensor because of several advantages including long life expectancy, relatively stable, high durability, resistance to corrosive gases, and good mechanical resistance. Performance improvement of CO gas sensor has been carried out by synthesizing SnO2 by polyol technique to produce nanostructured powder followed by deposition on alumina substrate using doctor blade coating technique. In order to determine the performance of the sensor material, the sample was characterized using x-ray diffraction, scanning electron microscopy, and BETcalculation of N2 adsorption-desorption. The XRD analysis showed the tetragonal crystal phase of SnO2, and BET analysis result in 24, 53 m 2 /g surface area. Furthermore, SEM image showed the nanorod shape of SnO2 morphology with diameter 50nm–2 μm. Sensor characterization with 30 ppm CO gas showed that the sample can work in 150 o C working temperature with sensitivity of 52.84%.